The Hierarchical Structure and Construct Validity of the PID‐5 Trait Measure in Adolescence. Issue 2 (7th July 2013) - De Clercq, Barbara; De Fruyt, Filip; De Bolle, Marleen; Van Hiel, Alain; Markon, Kristian E.; Krueger, Robert F.
Abstract The DSM‐5 may be the first edition that enables a developmental perspective on personality disorders because of its proposal to include a trait assessment in the Axis II section. The current study explores the reliability, structure, and construct validity of the Personality Inventory for DSM‐5 (PID‐5; Krueger, Derringer, Markon, Watson, & Skodol, 2012) in adolescents, a measure that assesses the proposed DSM‐5 traits. A community sample of Flemish adolescents (N = 434; 44.7% male) provided self‐reports on the PID‐5 and the Dimensional Personality Symptom Itempool (DIPSI; De Clercq, De Fruyt, Van Leeuwen, & Mervielde, 2006). Results indicate an acceptable reliability for the majority of the PID‐5 facets and a tendency toward structural convergence of the adolescent PID‐5 structure with the adult proposal. Convergent validity with age‐specific facets of personality pathology was generally supported, but discriminant validity appeared to be low. Beyond the findings that support the applicability of the PID‐5 in adolescents, developmental issues may be responsible for specific differences in the adolescent PID‐5 structure, the rather poor discriminant validity of the PID‐5, and the lower reliability of a small number of PID‐5 facets. These results indicate that further research on the validity of the PID‐5 in younger age groups is required.